The Civility of Civil Society: Collective Actions and Legitimacy From a Human Rights Perspective - Rodríguez Fuentes, Óscar Daniel (2019)
Civil society has been studied from elements that conformed it, however, only a small part of literature, studies civility of civil society. This supposes that associations, collectives, and social movements generate collective actions, positive social capital, and public discourse according to promotion and protection of human rights.